Science policy at the crossroads of global change research: Mongolia - Enkhamgalan Damiran; Tsevelmaa Khyargas; Nymadawa Pagbajabyn; Shairii Batsukh (Proceedings of the Mongolian Academy of Sciences, 2021)
In the last more than half a century, the science policies of countries have been interchanging in a cyclical manner between science, technology and innovation policies. In the early period of the evolution of the science policy, priority attention was given to policy matters, and the process of new knowledge generation proceeded at a rapid pace. Highly industrialised countries directly linked science policy with the growth and development of industry, and innovation gradually became the key catalyst of industrial development. But in the developing countries, science policy had a mixed impact on the process of industrialisation, where decision making by the Government had had a powerful impact on their science policy. Science is involved in the introduction and domestication of new knowledge in the education sector, experimentation and application of technology in local development, and guiding the government on its decisions that are economically efficient, environmentally safe, and promotes equality in the society. In this sense, if we regard scientific research as the key resource of “research industry,” then countries need to define a science strategy and policy that would meet this supply and demand, identify and apply the competitive edge of science. The main objective of this study is to evaluate the science policy of Mongolia in the last 50 years in the context of global change based on facts, and to compare it with the historical experience of science policy development in industrialised countries.